2019
DOI: 10.3390/galaxies7010014
|View full text |Cite
|
Sign up to set email alerts
|

Two-Temperature Magnetohydrodynamics Simulations of Propagation of Semi-Relativistic Jets

Abstract: In astrophysical jets observed in active galactic nuclei and in microquasars, the energy exchange rate by Coulomb collision is insufficient for thermal equilibrium between ions and electrons. Therefore, it is necessary to consider the difference between the ion temperature and the electron temperature. We present the results of two-temperature magnetohydrodynamics(MHD) simulations to demonstrate the effects of Coulomb coupling. It is assumed that the thermal dissipation heats only ions. We find that the ion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…This simplified prescription smooths over the microphysics, which depend on magnetic reconnection and shock properties; however, it does provide some handle on how the electron and ion populations must differ within a particular model to produce a specific emission property, albeit in a parameterized fashion. A recent study of electron heating in AGN jets (Ohmura et al 2019(Ohmura et al , 2020 has demonstrated that Ti/Te can become as large as 10 − 100 depending on the heating physics. In these simulations, shocks led to ion heating while weak Coulomb coupling prevented the ion and electron populations from equilibrating.…”
Section: Effects Of Two-temperature Plasmamentioning
confidence: 99%
“…This simplified prescription smooths over the microphysics, which depend on magnetic reconnection and shock properties; however, it does provide some handle on how the electron and ion populations must differ within a particular model to produce a specific emission property, albeit in a parameterized fashion. A recent study of electron heating in AGN jets (Ohmura et al 2019(Ohmura et al , 2020 has demonstrated that Ti/Te can become as large as 10 − 100 depending on the heating physics. In these simulations, shocks led to ion heating while weak Coulomb coupling prevented the ion and electron populations from equilibrating.…”
Section: Effects Of Two-temperature Plasmamentioning
confidence: 99%
“…Regarding the observations, the synchrotron mechanism was not deemed suitable to explain the flat-radio spectrum component from Cygnus X-1 [30]. Some suggested mechanisms include the optically thin free-free emission from a thermal plasma [32,33] or the combination of synchrotron (or another) mechanism with a thermal component [30].…”
Section: Resultsmentioning
confidence: 99%
“…The electron distribution function was assumed to be thermal. Ohmura et al [38,39] demonstrated that large-scale active galactic nuclei (AGN) jets can produce a two-temperature plasma. Motivated by their findings and the possibility that a two-temperature plasma will be produced due to shocks at the jet head and within the jet itself, we tested a simple two-temperature jet model by scaling the electron temperature relative to the ion temperature via the plasma temperature ratio:…”
Section: Ghz Emissionmentioning
confidence: 99%